Esophageal Cancer Prevention, Diagnosis and Therapy - Saba, Nabil F.; El-Rayes, Bassel F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book reviews the recent progress made in the prevention, diagnosis, and treatment of esophageal cancer. Epidemiology, molecular biology, pathology, staging, and prognosis are first discussed. The radiologic assessment of esophageal cancer and the role of endoscopy in diagnosis, staging, and management are then described. The principles of surgical resection, radiation therapy, and systemic chemotherapy for esophageal cancer are explained, and particular attention is paid to the multidisciplinary management of early-stage cervical, thoracic, distal, and junctional tumors. Up-to-date information is also provided on the treatment of metastatic and recurrent disease and on approaches that may affect future care, such as chemoprevention.   Esophageal cancer remains one of the least studied cancers although it accounts for more than 400,000 deaths across the globe each year. The majority of esophageal cancers worldwide are squamous cell carcinomas, yet in the past few decades major epidemiologic changes have occurred affecting the incidence of adenocarcinomas in Western countries. Despite the advances in surgical and non-surgical therapies, overall survival has not changed significantly. It is hoped that Esophageal Cancer: Prevention, Diagnosis and Therapy will assist specialists from a variety of disciplines, including surgery, radiation therapy, gastroenterology, and medical oncology, in delivering optimal, up-to-date care to the benefit of patients.
Epidemiology and risk factors for esophageal cancer -- Cellular and molecular biology of esophageal cancer -- Pathology of premalignant and malignant disease of the esophagus -- Barrett’s esophagus diagnosis and management -- Chemoprevention for esophageal carcinoma -- Esophageal cancer staging and prognosis -- Radiologic assessment of esophageal cancer.- Role of endoscopy in the diagnosis, staging and management of esophageal cancer.- Principles and approaches in surgical resection of esophageal cancer -- Principles of  radiation therapy for esophageal cancer -- Principles of systemic chemotherapy for esophageal cancer -- The multidisciplinary management of early stage cervical esophageal cancer -- The multidisciplinary management of early stage thoracic esophageal cancer -- The multidisciplinary management of early stage distal esophageal and gastroesophageal cancer.- Systemic treatment for metastatic or recurrent  disease -- Quality of life in patients with esophageal cancer.
Keywords: Oncology .; Pathology; Radiotherapy; Surgery; Oncology; Pathology; Radiotherapy; Surgery